1996
DOI: 10.1093/infdis/174.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Memory Cytotoxic T Lymphocyte Responses in Human Immunodeficiency Virus Type 1 (HIV-1)-Negative Volunteers Immunized with a Recombinant Canarypox Expressing gp160 of HIV-1 and Boosted with a Recombinant gp160

Abstract: A vaccine against human immunodeficiency virus (HIV) should induce virus-specific cytotoxic T lymphocyte (CTL) activity. Immunization of uninfected volunteers with a canarypox virus expressing HIV envelope was carried out in a phase I trial. Two injections of canarypox expressing HIV-1MN gp 160 (months 0 and 1) were followed by two boosts of recombinant envelope protein (months 3 and 6). HIV envelope-specific CTL were detected in peripheral blood mononuclear cells stimulated with autologous HIV-1-infected blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…To date, envelope subunit protocols, even in the context of novel adjuvants, have elicited very few MHC class I-restricted CD8 ϩ CTL responses. Live vector vaccine protocols using recombinant poxvirus constructs have, on the other hand, produced detectable CTL responses in a significant number of vaccinees (17,19,21,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, envelope subunit protocols, even in the context of novel adjuvants, have elicited very few MHC class I-restricted CD8 ϩ CTL responses. Live vector vaccine protocols using recombinant poxvirus constructs have, on the other hand, produced detectable CTL responses in a significant number of vaccinees (17,19,21,22).…”
Section: Resultsmentioning
confidence: 99%
“…Second generation vaccines using live, recombinant, poxvirus constructs have proven to be far more potent CTL immunogens (17)(18)(19). In recently instituted protocols, canarypox (ALVAC)-based vectors have been shown to elicit CTL activity in a significant number of volunteers (20)(21)(22), particularly in conjunction with a ''prime boost'' strategy involving initial vector immunization followed by a subunit boost. In the present study, we examined for the first time the ability of CTL elicited by clade B-based vaccines to lyse autologous CD4 ϩ lymphocytes infected with HIV-1 primary isolates representing six genetically diverse virus clades.…”
mentioning
confidence: 99%
“…The strategy of priming with ALVAC containing a single HIV env gene and boosting with rgp120 elicited cumulative envelope-specific CTL responses in over one third of seronegative vaccine recipients (7,16). When a multivalent canarypox vector was used, 61% of the seronegative vaccine recipients had a CTL response detected at least one time point postvaccination (12).…”
Section: Vol 76 2002mentioning
confidence: 99%
“…It had been demonstrated that this strategy was safe in uninfected (12) as well as HIV-1-infected individuals (40). Furthermore, these earlier constructs were also capable of generating some degree of humoral and cellular immunity in seronegative individuals (1,7,16).…”
mentioning
confidence: 99%
“…Fax j34 91 585 4506. e-mail mesteban!cnb.uam.es humoral and T-cell responses specific for this HIV antigen (Cooney et al, 1993 ;Graham et al, 1993 ;McElrath et al, 1994 ;Pioloux et al, 1995 ;Egan et al, 1995 ;Fleury et al, 1996). Most of these reports describe an enhancement of the anti-Env immune response when individuals primed with a poxvirus recombinant were boosted with purified recombinant gp160.…”
Section: Introductionmentioning
confidence: 99%